The Impact of Liquidity, Liabilities, and Equity on Bank Profitability - Syahputri, Andini; Niswa, Khairun; Ginting, Lita Hepika; Nasution, Fadillah; Aliah, Nur (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This study aims to examine the role of liabilities in the financial structure of the banking sector and their implications for bank liquidity, solvency, and profitability through a literature review approach. The research method employed is a library study that analyzes relevant national journal articles published in recent years. Data analysis was conducted using content analysis by comparing and synthesizing the findings of previous studies. The results indicate that liabilities constitute the primary source of bank funding and are closely associated with liquidity and solvency risks. Partially, liabilities do not always have a significant effect on bank profitability; however, simultaneously with equity, liabilities contribute to overall bank financial performance. The conclusion of this study emphasizes that prudent liability management, balanced with assets and equity, is a crucial factor in maintaining banking stability and sustainability.